Definition of the induction time for CO2 and CH4 hydrate via evaluation of the heat released during the process and the gas consumption rate. Issue 1 (1st December 2022) - Gambelli, A M; Filipponi, M; Rossi, F
Abstract: The induction period is defined as the time required to obtain a detectable quantity of hydrates during their natural or artificial production. This period includes the initial nucleation phase and part of the following massive growth phase. Several methods were thought to measure its length: the most adopted are the visual observation of the process and the direct measure of the temperature increase. However, these techniques are not always feasible and their accuracy is often low. This work deals with the definition of the induction time by considering the heat produced during the process, which is proportional to the temperature but significantly less affected by the stochastic nature of the process. In order to prove the feasibility of the process, the results were then compared with what obtained by considering the gas consumption rate to measure the induction time. The proposed method was validated for methane hydrates. The same confirmation was not possible for carbon dioxide hydrates, due to the high solubility in water of this species and the consequent overestimation of the gas consumption during the process.